QUILTING ART HISTORY IN AMERICA - Xolmurodova, Olima (Журнал иностранных языков и лингвистики, 2021)
In this article, the authors provide extensive information on the history and developmental stages of the art of American quilting. At the same time, important ideas about the importance of quilting art were noted